Perilaku Berisiko Terhadap Kesehatan Pada Mahasiswa IKM Angkatan 2018 Universitas Negeri Manado Tahun 2020 - Andi Sani, Sartika (Kampurui Jurnal Kesehatan Masyarakat, 2021)
Students are part of youth who are full of curiosity, looking for identity, need direction to be independent. Some of the health problems that occur in adolescents are related to risky behavior, namely smoking, drinking alcoholic beverages, drug abuse, and having premarital sexual relations. This study aims to determine the description of risk behavior towards health among students of Public Health Sciences, Manado State University, batch 2018 which includes smoking behavior, pre-marital sex behavior, drinking alcoholic behavior and drug abuse behavior. This research is a quantitative research. This type of research is a survey with a descriptive approach that aims to provide an overview of risky behavior towards health. The population in this study were all students of the 2018 IKM UNIMA class. The sample in this study were 141 new students registered at IKM UNIMA 2018. Data were collected using a questionnaire. The risk behavior of students at IKM Unima Study Program related to smoking showed that there were 13 people (18.6%) who had smoked and 12 of them still smoked (92.3%). Premarital sex behavior of IKM Unima Study Program students was obtained in the form of dating behavior as much as 87.1% with dating activities generally 48.6% had kissed the cheek and there were 2.9% who claimed to have had sex. The alcohol consumption behavior of students of IKM Unima Study Program found that 41.4% had ever consumed alcohol. Drug abuse behavior of IKM Unima Study Program students was never found to have consumed drugs. The results of this study are expected to provide input regarding the description of risky behavior in adolescence and the problems that need to be addressed immediately, as well as provide input to the Public Health Science Study Program and the Health Office to develop appropriate health promotion strategies for adolescents.